2018
DOI: 10.3389/fnins.2018.00518
|View full text |Cite
|
Sign up to set email alerts
|

Intravenously Injected Amyloid-β Peptide With Isomerized Asp7 and Phosphorylated Ser8 Residues Inhibits Cerebral β-Amyloidosis in AβPP/PS1 Transgenic Mice Model of Alzheimer’s Disease

Abstract: Cerebral β-amyloidosis, an accumulation in the patient’s brain of aggregated amyloid-β (Aβ) peptides abnormally saturated by divalent biometal ions, is one of the hallmarks of Alzheimer’s disease (AD). Earlier, we found that exogenously administrated synthetic Aβ with isomerized Asp7 (isoD7-Aβ) induces Aβ fibrillar aggregation in the transgenic mice model of AD. IsoD7-Aβ molecules have been implied to act as seeds enforcing endogenous Aβ to undergo pathological aggregation through zinc-mediated interactions. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…Thus, isomerized Aβ 42 due to a greater tendency to aggregation has greater neurotoxicity than Aβ 42 [ 40 ], accelerating plaque formation in a mouse model of Alzheimer’s disease [ 39 ]. At the same time, phosphorylation can reduce the pathogenic effect of the isomerized isoform [ 41 , 42 ]. The Aβ 40 isoform is considered to be more physiological than Aβ 42 , and the Aβ 40 /Aβ 42 ratio is used as one of the AD markers [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, isomerized Aβ 42 due to a greater tendency to aggregation has greater neurotoxicity than Aβ 42 [ 40 ], accelerating plaque formation in a mouse model of Alzheimer’s disease [ 39 ]. At the same time, phosphorylation can reduce the pathogenic effect of the isomerized isoform [ 41 , 42 ]. The Aβ 40 isoform is considered to be more physiological than Aβ 42 , and the Aβ 40 /Aβ 42 ratio is used as one of the AD markers [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, isomerization leads to an increase in Aβ 42 cytotoxicity [ 40 ]. However, if the Ser8 residue is phosphorylated, then the amyloidogenic effects of isoD7-Aβ 42 are neutralized [ 41 ]. Phosphorylated Aβ reduces zinc-dependent oligomerization and the amount of amyloid plaques in the brain of animals with AD [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…When developing inhibitors of the interaction between Na,K-ATPase and Aβ 42 , it is also necessary to take into account that there are Aβ 42 isoforms in the body system that differ in their pathogenic potential. Thus, the D7 isomerized isoform of Aβ 42 , which has a greater tendency to oligomerize in the presence of zinc, has greater cytotoxicity [ 8 ] and accelerates the development of amyloid plaques in a mouse model of AD [ 44 ]. At the same time, the phosphorylated form of pS8-Aβ 42 does not have the ability to inhibit Na,K-ATPase and reduced the rate of plaque formation in a mouse model of AD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the cellular environment also created the necessary conditions for the formation of dityrosine bonds [ 127 ], which may explain the higher stability of Aβ oligomers isolated from the brain or obtained from cell cultures compared to synthetic ones. On the contrary, Aβ phosphorylation at Ser8 reduces the aggregation ability of Aβ both in vitro and in a mouse model of AD [ 128 , 129 ].…”
Section: Factors Behind the Different Properties Of Brain-derived Cel...mentioning
confidence: 99%